2012
DOI: 10.1021/ef3007454
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Structural Features of Humins Formed Catalytically from Glucose, Fructose, and 5-Hydroxymethylfurfuraldehyde

Abstract: The IR spectra of humins formed during the acid-catalyzed conversion of glucose, fructose, and 5hydroxymethylfurfuraldehyde were compared. The spectra are quite similar except for three groups of features that can be attributed to furan rings and carbonyl groups conjugated with carbon−carbon double bonds. IR spectroscopy further revealed that benzyl groups could be added to the humins as they formed or in a separate aldol addition/condensation reaction after they had been recovered. The IR spectra are consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
321
4
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(357 citation statements)
references
References 48 publications
27
321
4
5
Order By: Relevance
“…Both the model in this study and the model proposed by Girisuta and co-workers (2013) could fit the experimental data very well by using the modified parameter fitting method. However, according to the studies of Patil et al (2012) and Van et al (2013) about humins, the model in the present study should be more reasonable.…”
Section: Comparisons With Other Modelsmentioning
confidence: 89%
See 3 more Smart Citations
“…Both the model in this study and the model proposed by Girisuta and co-workers (2013) could fit the experimental data very well by using the modified parameter fitting method. However, according to the studies of Patil et al (2012) and Van et al (2013) about humins, the model in the present study should be more reasonable.…”
Section: Comparisons With Other Modelsmentioning
confidence: 89%
“…The maximum yield of LA was obtained at 150 °C and 0.8 mol/L H2SO4 at 58.0 mol%. Based on the study of Patil (2012) and Van (2013), the mechanism of the formation of humins, the authors proposed the kinetic model that contained four consecutive irreversible first-order reactions under the assumption that humins could be only converted by 5-HMF. A very good fit was observed between the experimental data and the kinetic model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For hydrothermal treatment of fructose in the absence of any additional catalysts at 120-140 ℃, Yao et al [5] proposed that fructose first undergoes intramolecular dehydration to HMF, and HMF further polymerizes to form carbon spheres, which contain a dense hydrophobic carbon core and a hydrophilic shell according to field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM) images. For H 2 SO 4 -catalyzed fructose conversion at 135 ℃, Patil et al [6] suggested that fructose must first be converted to 2,5-dioxo-6-hydroxyhexanal (DHH), which subsequently undergoes aldol addition and condensation to form humins. For hexose derived humins catalyzed by H 2 SO 4 at higher temperature of 180 ℃, van Zandvoort et al [7] inferred a polyfuranic molecular structure, wherein the inclusion of DHH and limited LA occurs through aldol condensations with the aldehyde groups of HMF or DHH itself.…”
Section: Introductionmentioning
confidence: 99%